Fast Ion Conduction of Sintered Glass-Ceramic Lithium Ion Conductors Investigated by Impedance Spectroscopy and Coaxial Reflection Technique. Issue 14 (21st October 2020) - Samsinger, R. F.; Letz, M.; Schuhmacher, J.; Schneider, M.; Roters, A.; Kienemund, D.; Maune, H.; Kwade, A.
Abstract : As the ionic conductivity of solid-state lithium ion conductors rises, knowledge of the detailed conductivity mechanisms is harder to obtain due to the limited frequency resolution of the traditional impedance spectrometers. Moreover, the data is easily affected by the local microstructure (i.e. pores, grain-boundaries) and the preparation conditions. The aim of this work is to demonstrate the feasibility of the coaxial reflection technique as a reliable tool to study fast ionic conductors (i.e. σ > 10 −4 S cm −1 ). Especially the relative permittivity can be determined more accurately at room temperature. For the first time the electrical performance of LATP and LLZO manufactured via a scalable top-down glass-ceramic route is evaluated. The density turns out to be a key parameter influencing both relative permittivity and resulting conductivities. For a 100% dense LATP sample the coaxial reflection technique reveals a high grain-core conductivity of 6 × 10 −3 S cm −1 similar to the conductivity of ideal single crystals.